ASAS BEST INTEREST OF THE CHILD SEBAGAI PARAMETER UTAMA HAK ASUH DI PENGADILAN AGAMA (ANALISIS NORMATIF DAN YURISPUDENSI) - Muchammad Abdul Basir; Zanuar Anwari; Hartono (Al-Usroh : Jurnal Hukum Keluarga Islam, 2025)
The application of the Best Interest of the Child principle in custody determinations is a critical issue, as it directly affects children’s welfare and the quality of legal protection in family disputes. Variations in judicial practices and inconsistencies between legal norms and judicial considerations indicate the need for a more in-depth examination of the principle’s effectiveness. This paper aims to evaluate the consistency of the application of the best interests principle in the Religious Courts through a normative–empirical approach, while also identifying gaps between regulatory frameworks, judicial practices, and the actual conditions experienced by children following custody decisions. This study employs a qualitative method, including normative analysis of child protection regulations, a jurisprudential review of court decisions, limited interviews, and an examination of empirical data concerning children’s conditions. The findings reveal that although the best interests principle serves as a strong legal foundation, its implementation remains influenced by the absence of objective assessment standards, variations in judicial reasoning, and the limited involvement of professional assessors. The study further confirms that custody decisions prioritizing children’s needs have a positive impact on their physical, emotional, and social development. Therefore, the formulation of technical guidelines and the involvement of relevant experts are necessary to ensure more consistent and child-centered custody rulings.